Clinicopathologic significance of DNA mismatch repair protein status in endometrial cancer - Ju-Hyun Kim; Byung-Su Kwon; Hyojin Kim; Dong Hoon Suh; Kidong Kim; Yong Beom Kim; Jae Hong No (Elsevier, 2022)
Objective: The prognostic implications of DNA mismatch repair protein (MMRP) have not been determined in endometrial cancer. Therefore, in this study, we aimed to evaluate the clinicopathologic characteristics of DNA MMRP deficiency in endometrial cancer. Materials and methods: We examined the MMRP status of 206 patients with endometrial carcinomas, using immunohistochemistry, and analyzed their clinicopathologic factors and survival outcomes stratified by MMRP status using the Kaplan-Meier method and Cox regression analysis. Results: Forty-three cases were deficient for at least one MMRP (20.9%). Loss of MLH1 was the most common (13.1%), followed by MSH6 (7.8%). MMRP deficiency was significantly associated with lympho-vascular space invasion, deep myometrial invasion, and adjuvant treatment (P = 0.032, 0.041, and 0.047, respectively). MMRP-deficient patients had a better overall survival (OS), particularly at advanced cancer stages (III/IV) (100% vs. 73.7%, P = 0.170) or if they had received adjuvant treatment (100% vs. 86.7%, P = 0.087). Conclusion: Although MMRP deficiency was associated with unfavorable prognostic risk factors in endometrial cancer, we found a trend in favor of OS in MMRP-deficient patients. More studies are needed to confirm its prognostic implication.